The fundamentals of design management - Best, Kathryn (AVA Academia ; La Vergne, TN : Distributed in the USA & Canada by Ingram Publisher Services, 2010)
A guide to managing the people, projects, processes and procedures behind the design of our everyday products, services, environments and experiences. It is suitable for those from various backgrounds such as art and design, business, marketing or media.